Desarrollo del vástago vegetativo en Coffea arabica L. cv. bourbon Choussy. IV. Desarrollo del procambium y los tejidos vasculares de la hoja - Fournier O., Luis A. (1965)
The origin and differentiation of vascular tissues in the leaf of Coffea arabica L. cv. bourboun Choussy is described. Procambium and phloem differentiate continuously and acropetally in all veins, whereas xylem differentiation begins in isolated strands. The first xylem elements appear in tne middle third of the midvein, the same area in which first procambial strands differentiate in the secondary veins. Differentiation of secondary veins and those of lower ranks gives rise to a complicated vein network, in which all increase in size is due to intercalary growth. No phloem elements were observed in the endings of minor veins.